Cyber Pedagogy and Student Wellbeing: A Literature Review on Digital Burnout and Mental Health in Online Learning - Tari, I Dewa Ayu Eka Purba Dharma; Mahaardhika, I Made (The Indonesian Institute of Science and Technology Research, 2025)
This study examines the relationship between cyber pedagogy, digital fatigue, and students' mental health in online learning through the Literature Review (LR) approach. Based on an analysis of the selected literature from 2019 to 2025, it was found that digital burnout and mental health disorders are serious challenges in online education. Cyber pedagogy can reduce psychological distance and strengthen student well-being by balancing structure, dialogue, and learning autonomy. Data was obtained from academic journals and analyzed using content analysis. This research emphasizes the importance of humanistic pedagogical approaches in digital learning design. These findings provide conceptual and practical contributions for educators and policymakers to create a mentally healthy online learning ecosystem.